Epistaxis in Adults: Management and Outcome - Saif Saeed; Jaafar Kadhim (The Iraqi Journal of Medical Sciences)
Background: Epistaxis is defined as bleeding from the nose. It is the most common emergency encountered by otolaryngologists. It affects all age groups and both genders. Several different modalities can be used to control nose bleeds. Objective: To study the association of different health conditions with epistaxis, effectiveness of emergency interventions to control it, and the outcome of each approach. Methods: One hundred eighteen patients with epistaxis were selected during the period of one year. Examination was done for all patients after securing the airway to determine the site of bleeding followed by the proper management. Different managements were studied for efficacy and outcome. Results: The mean age for epistaxis was 53.81 years with 71.2% of patients being older than 45 years, male to female ratio was 1.68:1. There was a strong association between the incidence of epistaxis and increasing age (P = 0.002) with male predominance. The anterior septum was the most implicated area in epistaxis (58%). The most commonly encountered intranasal pathology was a deviated nasal septum (25.4%). The most commonly associated systemic disease with epistaxis was hypertension (43%). Forty one percent of the patients were on anticoagulants. Collectively, only 25.4% of epistaxis were idiopathic in nature. The most commonly used intervention to stop the bleeding was silver nitrates cauterization (45%). Ninety two percent of the patients underwent a non-surgical method to stop the bleeding, and 78% underwent a direct approach. Most failures were observed in endoscopic assisted cauterization (41.6%). Seventy five percent were treated in an outpatient setting, while the rest were hospitalized. The use of a direct approach for epistaxis management was associated with significantly lower hospitalizations (P <0.001). Conclusion: Epistaxis affects adults in all age groups and incidence increases with age. The bleeding can be associated with a nasal pathology and/or a systemic abnormality. Epistaxis should be managed with a direct approach whenever possible to minimize hospitalizations. Keywords: Adults' epistaxis, endoscopic assisted cauterization, nasal packing Citation: Saeed SS, Kadhim JM. Epistaxis in adults: Management and outcome. Iraqi JMS. 2024; 22(1): 103-114. doi: 10.22578/IJMS.22.1.12